Seasonal Influenza Vaccine Effectiveness in People With Asthma: A National Test-Negative Design Case-Control Study. (5th November 2019) - Vasileiou, Eleftheria; Sheikh, Aziz; Butler, Chris C; Robertson, Chris; Kavanagh, Kimberley; Englishby, Tanya; Lone, Nazir I; von Wissmann, Beatrix; McMenamin, Jim; Ritchie, Lewis D; Schwarze, Jürgen; Gunson, Rory; et al.
Abstract: Background: Influenza infection is a trigger of asthma attacks. Influenza vaccination can potentially reduce the incidence of influenza in people with asthma, but uptake remains persistently low, partially reflecting concerns about vaccine effectiveness (VE). Methods: We conducted a test-negative designed case-control study to estimate the effectiveness of influenza vaccine in people with asthma in Scotland over 6 seasons (2010/2011 to 2015/2016). We used individual patient–level data from 223 practices, which yielded 1 830 772 patient-years of data that were linked with virological ( n = 5910 swabs) data. Results: Vaccination was associated with an overall 55.0% (95% confidence interval [CI], 45.8–62.7) risk reduction of laboratory-confirmed influenza infections in people with asthma over 6 seasons. There were substantial variations in VE between seasons, influenza strains, and age groups. The highest VE (76.1%; 95% CI, 55.6–87.1) was found in the 2010/2011 season, when the A(H1N1) strain dominated and there was a good antigenic vaccine match. High protection was observed against the A(H1N1) (eg, 2010/2011; 70.7%; 95% CI, 32.5–87.3) and B strains (eg, 2010/2011; 83.2%; 95% CI, 44.3–94.9), but there was lower protection for the A(H3N2) strain (eg, 2014/2015; 26.4%; 95% CI, −12.0 to 51.6). The highest VE against all viral strains was observed in adults aged 18–54 years (57.0%; 95% CI, 42.3–68.0). Conclusions: Influenza vaccination gave meaningful protection against laboratory-confirmed influenza in people with asthma across all seasons. Strategies to boost influenza vaccine uptake have the potential to substantially reduce influenza-triggered asthma attacks. Abstract : This test-negative design, case-control study found that over 6 seasons, influenza vaccination protected people with asthma against laboratory-confirmed influenza. Protection was highest among younger adults (18–54 years). For older adults (>65 years), protection was only provided against influenza B.